Determination of the parameters of spherical and cylindrical surfaces with multichannel phase svetodalnomerov - Шмаров, В.Н. (Proceedings of National Aviation University (archive), 2006)
The operation of four-channel and five-channel phase light distance measurement devices surveyed. Is shown, that with the help of such measuring systems restoring the shape a large-sized plants of the spherical and cylindrical shape is possible.